The Lintner model revisited: Dividends versus total payouts - Christian Andres; Markus Doumet; Erik Fernau; Erik Theissen (University of Cologne, Centre for Financial Research (CFR), 2013)
We analyze how the introduction of repurchases in 1998, and a major tax reform in 2001, affected the payout policy of German firms. To this end, we estimate Lintner (1956) partial adjustment models for both dividends and total payouts. We also analyze the implications for payout of changes in both permanent and transitory earnings. Our results are inconsistent with the hypothesis that dividends and repurchases are perfect substitutes. They are also inconsistent with the prediction that tax considerations are a major driver of payout decisions. Our results instead support the flexibility hypothesis that predicts that dividends are used to disburse permanent, and repurchases transitory, earnings.
Keywords: G32; G35; 330; Dividends; Repurchases; Lintner model